Anemia affects one in four Indian men and has not decreased in the last decade: Trends, geographic variability and predictors from nationally representative data, 2005 to 2016 - Pant, Anjali; Scott, Samuel P.; Nguyen, Phuong Hong; Yadav, Kapil; Menon, Purnima (American Society for Nutrition, 2020)
Men have largely been ignored in anemia-focused research and policies. We sought to examine trends, geographic variability, and predictors of anemia in Indian men between 2005 and 2016.